2015
DOI: 10.1007/s13197-015-1840-1
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of whey and casein protein- effect on functional, rheological, textural and sensory properties of breads

Abstract: Milk proteins were hydrolyzed by papain and their effect on the rheological, textural and sensory properties of bread were investigated. Water absorption capacity, emulsification capacity, foam volume, foam stability and solubility of Whey and casein protein concentrates and their hydrolysates were determined. The farinograph parameters of wheat flour and blends of wheat flour with casein and whey protein and their hydrolysates were determined to evaluate changes in water absorption capacity, dough development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 32 publications
(34 reference statements)
3
38
2
Order By: Relevance
“…Furthermore, increases in peak viscosity and gelatinization temperature were observed in composite flours of wheat, cereals, legumes, or sago flours [ 30 – 33 ]. By contrast, other reports have indicated that addition of legumes protein isolates and milk proteins reduced the peak viscosity of the dough [ 34 , 35 ]. The difference could be attributed to the variation in the added materials that in the latter is protein isolates which are devoid of sugars or starches whereas in the former the whole materials are added which might contains sugars and starches that increase the viscosity and gelatinization temperature.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, increases in peak viscosity and gelatinization temperature were observed in composite flours of wheat, cereals, legumes, or sago flours [ 30 – 33 ]. By contrast, other reports have indicated that addition of legumes protein isolates and milk proteins reduced the peak viscosity of the dough [ 34 , 35 ]. The difference could be attributed to the variation in the added materials that in the latter is protein isolates which are devoid of sugars or starches whereas in the former the whole materials are added which might contains sugars and starches that increase the viscosity and gelatinization temperature.…”
Section: Resultsmentioning
confidence: 78%
“…Schmiele et al (2017) reported a significant anti-retrogradation effect of soy protein hydrolysate in breads, which would be of interest in preventing the staling of bakery products. Gani et al (2015b) also found a decrease in breakdown and setback values when adding whey protein hydrolysate, as did Ondrani et al (2007) by adding whey protein concentrate.…”
Section: Pasting Propertiesmentioning
confidence: 77%
“…At higher percentages of substitution of both hydrolysates (>10%), it was possible to observe that flour hydration almost did not happen in the dough formation process, not enabling the conventional dough to take form, this way resulting in a more fluid dough. Gani et al (2015b), despite working with smaller proportions (up to 15%), also observed an increase in AT with the incorporation of hydrolyzed whey protein.…”
Section: Farinograph Propertiesmentioning
confidence: 79%
See 1 more Smart Citation
“…By adding soy protein to bread, both the total protein quantity and quality are thereby increased . However, addition of other ingredients than gluten proteins to bread will have a negative effect on the sensory quality of bread . According to Gani et al ., addition of milk proteins and their hydrolysates will affect the sensory quality, including crust and crumb color, texture and flavor.…”
Section: Introductionmentioning
confidence: 99%